Teologi Bisnis: Korporasi, Masalah HAM dan Mandat Penciptaan-Penyelamatan - Winibaldus Stefanus Mere (Jurnal Ledalero, 2021)
This article aims at framing a theological understanding about business in the context of the impacts of corporate conducts on human rights. The relevance of this theological understanding arises from the need to bring a true liberation (salvation) in a contradictory reality: human suffering due to human rights violation in business activities on the one hand and ineffectiveness of legal and moral instruments, as well as weak individual and collective commitments of government and business actors in dealing with that problem on the other hand. Using “creation, fall and redemption” approach as basis for biblical worldview to understand issues related to business and its social impacts, this article highlights the necessity of internal factors as foundational values that can bring about a true commitment to do business not only based on legal and moral norms as a mere socio-political consensus, but also as an expression of a socio-spiritual obedience to and faith in God. Because, more than just accumulating commercial benefits, business has mission to realize God’s work for human salvation in this world. Business actors as individuals and organization (corporation) become God’s collaborators – mainly in their nature as bearer of the Image of God and mandate of creation - to materialize the works of salvation in this world through their activities in the production and distribution of goods and services that respect human rights.Keywords: teologi bisnis, korporasi, hak asasi manusia, gambaran Allah, mandat penciptaan, penebusan, kapitalisme liberal